Pendidikan Islam di Singapura - Mohammad Kosim (IAIN Ponorogo, 2011)
This article describes the development of Islamic education in Singapore, especially Madrasah al-Juneid al-Islamiyah. The problem: how is the development of curriculum in Madrasah alJuneid? and what are the future challenges this madrasah? To answer this problem, the amount of data collected through observation methods, interviews, and documentation. The data collected were analyzed by descriptive-qualitative. The results showed: first, the curriculum in Madrasah al-Juneid initially uncharged pure religion then expanded by adding a general lesson. In learning, study materials commonly used approach to integration with the teachings of Islam. Second, the madrasahs in Singapore face challenges in the future are not light, namely the world of work demands, the demands of quality, the challenge of Western lifestyles, and the accusations against Islam as a religion of terrorists. All these challenges must be responded by madrasah creative in developing a quality program that graduates could compete with graduate school; can fortify the modern-secular lifestyle, and can coexist peacefully in the midst of Singapore's plural society.